Kepemimpinan Orangtua dalam Mendidik Anak Melalui Unggah-ungguh Basa dan Basa Semu di Lingkungan Masyarakat - Effendi, Kusno (Universitas Ahmad Dahlan, 2015)
Educational leadership is the influence of an educational leader in educating a child by moving, directing, motivating, and balance to achieve educational goals. This research includes issues related to the leadership of parents in educating children, the quality of leadership of parents in educating children, leadership success of parents in educating children, leadership type of parents to educate children, the barriers parents in leadership to educate children and use unggah-ungguh basa and basa semu in educating children. The research method uses qualitative research approach. The number of research subjects 6 people taken by purposive sampling. The technique of collecting data using an unstructured interview. The validity of the data collection tool using triangulation techniques with the examination of the source data. Analysis and interpretation of the data based on the criteria. The Conclusion of the study: 1) Leadership parents educate children in unggah ungguh basa and basa semu less active, less qualified and did not succeed. 2) Parents are not active in providing education leadership to children, 3) parents are less qualified to educate the leadership of children, 4) Parents inactive, less qualified and did not succeed in educating although understanding ungguh upload-alkaline and alkaline quasi-5) Type leadership of parents to educate children in upload-ungguh base in the village community Gilangharjo, Pandak, Bantul is the type of permissive. The research can be used as a guide in developing a curriculum based on cultural values, including local culture, which affects the moral development of children